Electrolysis of ammonia in aqueous solution by platinum nanoparticles supported on carbon nanotube film electrode. (1st May 2020) - Hanada, Nobuko; Kohase, Yusuke; Hori, Keisuke; Sugime, Hisashi; Noda, Suguru
Abstract: Electrolysis of ammonia in an aqueous solution can generate hydrogen gas at room temperature. An anode reaction of nitrogen gas desorption on ammonia electrolysis has a much larger overvoltage than that of a cathode reaction, and one of the useful electrode catalysts for the anode reaction is platinum (Pt). In this study, in order to increase the surface area of Pt three-dimensionally, Pt nanoparticles are held on a sponge-like film of carbon nanotubes (CNTs) that has a large surface area of 5000–10000 cm 2 per 1 cm 2 of the CNT film. The electrodes were adapted to the ammonia electrolysis to increase the current density with a low overvoltage. The Pt nanoparticles were deposited on the CNTs by a polyol method at various temperatures, and the Pt nanoparticles supported on the CNT (Pt-CNT) electrodes were fabricated by vacuum filtration of the Pt-CNT dispersion. The size of the deposited Pt nanoparticles was approximately 2–3 nm. The maximum electrochemical surface area of the Pt nanoparticles was more than 250 cm 2 per unit electrode area of 1 cm 2 . The Pt-CNT film electrode with a large surface area of the Pt catalyst increased the current density of the anode reaction compared with the Pt plate or the Pt-black electrodes. The Pt-CNT decreased both the activation overvoltage corresponding to the high Pt surface area and the concentration overvoltage corresponding to the three-dimensional structure of the CNT films. Moreover, it is clarified that the deactivation of the catalysts by the anode reaction does not occur below −0.2 V (vs Hg|HgO) for the Pt-CNT electrodes.